Pulmonary artery thromboembolism in a critically ill neonate successfully treated using thrombolytic therapy - Gerson Valencia Villeda; Robert Spencer; Matthew A Crysta; Jeffrey D Dayton; Usha Krishnan (Wolters Kluwer Medknow Publications, 2021)
Pulmonary artery thromboembolism is a common and treatable cause of adult pulmonary hypertension. Although rare in children, if undiagnosed, it can result in significant morbidity and mortality. We report a case of a cyanotic neonate found to have bilateral pulmonary arterial thrombi who successfully underwent thrombolysis using tissue plasminogen activator with prompt resolution of right ventricular hypertension.